Monosemy in phraseological units in the Uzbek and English languages (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In the study of monosemy in phraseological units, it has been determined that there are not enough sources about monosemy and polysemy in phraseologisms. Despite those it is tried to be analyzed the linguistic theories consisting of lexical and contextual meaning of monosemantic and polysemantic phraseological units with the help of examples. Moreover, a comprehensive study of these phenomenon can give a broader atmosphere and good chance for in- depth analysis of various features of different systematic languages.